Missionary Christianity and local religion : American Evangelicalism in North India, 1836-1870 - Jones, Arun W. (Texas : Baylor university press, 2017)
Missionary Christianity and Local Religion provides portrayals and analyses of the ideas, motivations, and activities of the diverse individuals who formed and nurtured a flourishing North Indian Christian movement that was both evangelical and rooted in local religious and social realities. This exploration of new Christian communities created by the confluences and divergences between American evangelical and bhakti religious traditions reveals the birth and early growth of one of the many incarnations of Christianity.--Publisher.
The religious context in North India : Hinduism, Islam and Christianity -- The religious context in North India : American evangelicalism -- The missionaries : religious and social innovators -- Indian workers and leaders : negotiating boundaries -- Theology in a new context -- Community in a new context.
Includes bibliography (pages 287-310) and indexes.
Keywords: Missions, American -- India, North -- History; Christianity and other religions -- India, North; Christianity; Interfaith relations; Missions, American; India, North -- Church history; India, North; Church history; History